The role of the family in facilitating innovation and change: Family communication in forming the identity of the alpha generation - Rismayanti, Rismayanti; Mailin, Mailin; Rubino, Rubino; Khairuddin, Ahmad (Priviet Social Sciences Journal, 2026)
The digital era creates a complex environment for Generation Alpha, immersed in technology from birth. This study aims to investigate how families, through communication patterns, facilitate innovation and healthy identity formation amidst the pressures of digital culture. Using a qualitative approach with a multi-family case study design with six subjects, data were collected through in-depth interviews, participant observation, and analysis of communication artifacts. The results show that democratic and participatory communication patterns are significantly correlated with children's innovative capacity. Families that adopt a concept-oriented approach, emphasizing the exchange of ideas and the appreciation of differing opinions, are able to produce individuals with greater cognitive flexibility and resilience. Key findings identify psychological safety as a crucial mediator, enabling families to function as "identity laboratories" where children experiment with digital personas before consolidating authentic identities. The study concludes that transforming parents' roles into digital mentors is crucial for bridging the generation gap through active mediation. By integrating family values and digital influences, children can become thoughtful innovators and responsible digital citizens.